Reconstruction of a genome-scale metabolic model for Streptococcus zooepidemicus: Comparison with Corynebacterium glutamicum to study hyaluronic acid production - Zahra Nikuiyan; Fatemeh Tabandeh; Ehsan Motamedian; Saeed Salehi; Marjan Talebi; Rouzbeh Almasi Ghale (PLoS ONE, 2025)
Comparison of Streptococcus zooepidemicus ( S. zooepidemicus ) as a natural strain for hyaluronic acid (HA) production with Corynebacterium glutamicum ( C. glutamicum ) as a recombinant host is a valuable tool to identify key metabolic targets for enhanced HA production. For this purpose, a comparative analysis based on the genome-scale metabolic networks of native and recombinant HA producers was conducted. In this study, the first genome-scale metabolic model (GEM) of S. zooepidemicus , was reconstructed and named i ZN522 . This systematically curated model was validated using various biochemical data, consisting of growth rate prediction, amino acids auxotrophy, and different carbon sources consumption. Following the validation, key genes for HA overproduction in both bacteria were identified through iterative single-gene deletion analysis. Comparing optimal flux distributions predicted by models of S. zooepidemicus strain with recombinant C. glutamicum revealed that removing the oxidative pentose-phosphate pathway in C. glutamicum effectively increases the hyaluronan synthase flux. Additionally, improvement strategies in C. glutamicum primarily rely on up- and down-regulation, while in S. zooepidemicus , gene deletions can optimize the HA production rate. By comparing the two metabolic models, it can be inferred that eliminating of glucose-6-phosphate dehydrogenase enzymatic reaction in C. glutamicum results in greater similarity in the central carbon metabolisms of C. glutamicum and S. zooepidemicus , thereby enhancing HA production.